Incidence of Injuries to Major Blood Vessels in the Lower Limb - Abd-alla, Mohammad A; Mohammad, Saad A (AL-Kindy College Medical Journal, 2009)
Background: Blood vessels injury is one of the most common causes of medical emergencies that admitted to hospitals and at the same time it regarded as one of the most important causes of death. They may represent less than 15% of all injuries; they deserve special attention because of their severe complications. Objective: The aim of the present study is to assess anatomically the injures of major arteries and veins in the lower limb with their management. Methods: The present study extended from April 2006 to February 2007, in which 65 patients with lower limb vascular injury were examined in Emergency Department and Forensic Medicine Department of Tikrit Teaching Hospital in Salah-Aldin governorate. Diagnosis was made by clinical diagnosis alone, or in combination with angiography. Some surgical interferences as vascular repair was carried out, but if not possible the interposition graft was used by great saphenous vein for vascular reconstruction. Results: The total cases were 65 patients (49 males and 16 females), ranging from 16 years to 67 years with a mean age of 41.5±6.4 years. Penetrating trauma was the main cause of injury for 52 patients. Seventeen cases had bilateral limbs vascular injuries. Arterial injuries were most common in the femoral arteries, followed by the tibial and finally the popliteal arteries. Vascular repair were performed in 16 cases, while in 11 cases great saphenous vein interposition graft were done. There were 17 cases associated with venous injury, of which 11 cases had surgical vascular repair, and 6 had vein graft interposition. There were concomitant femur fractures in 2 cases, fibula fractured in 3, tibia fractured in 1 and the foot bones fractured in 3. Conclusion: Lower limb vascular injured patient should be transferred to vascular surgery centers as soon as possible. After first aid management, anticoagulant treatment may be started post operatively to prevent the propagation of the thrombosis. Early fasciotomy is done if there is any suspicion of occurrence of compartment syndrome.